ПОКРАЩЕННЯ ЯКОСТІ РЕГУЛЮВАННЯ АСИНХРОННОГО ЕЛЕКТРОПРИВОДА З КЕРУВАННЯМ ЗА РЕАКТИВНОЮ ПОТУЖНІСТЮ - Чепкунов, Р.А. (Інститут електродинаміки НАН України, Київ, 2025)
In addition to the known properties of an asynchronous electric drive with reactive power control - ensuring high speed in the entire multipolar speed control range, including zero, independence of mechanical torque from changes in the parameters of the asynchronous motor - the peculiarity of its operation at frequencies close to zero with a loaded motor is considered and an adaptation is proposed to ensure compliance with the set and actual speeds when changing the parameters of the asynchronous motor. The supplier of the electric drive can be Zaporozhye Electrical Equipment Plant, LLC "Electronics, LTD" can participate in the coordination of technical conditions. References 6, Figures 5.